Effects of wet corn gluten feed and dietary particle size on ruminal fermentation and milk production - Sullivan, M.L.; Bradford, Barry J. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2012)
Wet corn gluten feed (WCGF) was included in 4 diets at 0, 11, 23, and 34% of diet dry matter. Alfalfa hay was used to maintain at least 10% of particles ≥ 0.71 inches in length (the top screen of the Penn State Particle Separator) in all diets. Ruminal probes were placed in the rumens of 7 ruminally cannulated lactating Holstein dairy cows to measure ruminal pH. As WCGF increased in the diet, dry matter intake and milk production increased quadratically with 23% WCGF supporting the highest feed intake and milk yield. Ruminal pH and milk fat content were similar across all diets.
Dairy Research, 2010 is known as Dairy Day, 2010
Keywords: Dairy; Alfalfa; Dry matter intake; Milk yield; Wet corn gluten feed